Roles of DNA damage in renal tubular epithelial cells injury - Wang, Peipei; Ouyang, Jing; Jia, Zhanjun; Zhang, Aihua; Yang, Yunwen (Frontiers in Physiology, 2023)
The prevalence of renal diseases including acute kidney injury (AKI) and chronic kidney disease (CKD) is increasing worldwide. However, the pathogenesis of most renal diseases is still unclear and effective treatments are still lacking. DNA damage and the related DNA damage response (DDR) have been confirmed as a common pathogenic of AKI and CKD, according to recent investigations. Reactive oxygen species (ROS) induced DNA damage is one of the most common forms of DNA damage involved in the pathogenesis of AKI and CKD. In recent years, several developments have been made in the field of DNA damage. Herein, we review the roles and developments of DNA damage and DDR in renal tubular epithelial cell injury in AKI and CKD. In this review, we conclude that focusing on DNA damage and DDR may provide valuable diagnostic biomarkers and treatment strategies to renal diseases including AKI and CKD.